Synchronization in the second approximation - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2003)
It is well-known the phenomenon of synchronization (frequency entrainment) in self-excited systems subjected to external or parametric excitations; A lot of monographs [2, 3, 4] has analyzed several important systems for which the synchronization effect occurs and can be determined in the first approximation. However, there exist also certain systems possessing a stable-excited oscillation obtained in the first approximation, which may be synchronized only in the second approximation. This article deals with some systems of the mentioned type; the asymptotic method [1] is applied for this purpose.